ZAKAT AS LOCALLY-GENERATED REVENUE: ITS ACCOUNTING TREATMENT AT BAITUL MAL ACEH - Armiadi Musa (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
In Aceh, Indonesia, zakat is included as a locally-generated revenue (Pendapatan Asli Daerah – PAD) and it is managed by a government body called Baitul Mal. As a government institution, Baitul Mal is obligated to present financial statements according to Government Accounting Standards (Standar Akuntansi Pemerintah - SAP). This article reports the findings of the accounting treatment for zakat financial statements in Baitul Mal Aceh. Baitul Mal Aceh as the government zakat institution is annually required to disclose two different financial statements, both financial statements based on Government Accounting Standards (SAP) and based on a statement of financial accounting standards 109 (PSAK 109). Therefore, the purpose of this study is to investigate the compliance of Baitul Mal Aceh with SAP dan PSAK 109 in zakat financial reporting. This research is a descriptive study from the data obtained through field study. The results showed that Baitul Mal Aceh has implemented both SAP and PSAK 109 in presenting the financial statements regardless of some items that might not be in accordance with the standards. In financial statements based on SAP, a variance was found in the presentation of information related to the procurement of assets and the details of the depreciation. As for the financial statements based on PSAK 109, it has been presented from 2012 to 2017. From the available data, there are some differences in the disclosure compared to PSAK 109. Amil funds and non-halal funds were not disclosed in the balance sheet as well as there was no statement of changes in assets under management. Moreover, these financial statements were not presented in the last two years due to limited supporting facilities/devices and human resources.========================================================================================================Zakat sebagai Pendapatan Asli Daerah: Perlakuan Akuntansinya pada Baitul Mal Aceh. Di Aceh, Indonesia, zakat dimasukkan sebagai salah satu Pendapatan Asli Daerah (PAD) yang dikelola oleh sebuah institusi pemerintah yang disebut Baitul Mal. Sebagai badan pemerintah, Baitul Mal diwajibkan untuk membuat laporan keuangannya sesuai dengan Standar Akuntansi Pemerintah (SAP). Artikel ini menyajikan temuan dari perlakuan akuntansi pada laporan keuangan zakat di Baitul Mal Aceh. Baitul Mal Aceh sebagai lembaga amil zakat pemerintah diwajibkan menyajikan dua laporan keuangan yang berbeda setiap tahunnya, yaitu laporan keuangan menurut Standar Akuntansi Pemerintahan (SAP) dan menurut Pernyataan Standar Akuntasi Keuangan Nomor 109 (PSAK 109). Untuk itu, tujuan dari penelitian ini adalah untuk menginvestigasi kepatuhan Baitul Mal Aceh dengan SAP dan PSAK 109 dalam penyajian laporan keuangan zakat. Penelitian ini adalah studi deskriptif berdasarkan data yang diperoleh dari studi lapangan. Hasil penelitian menunjukkan bahwa Baitul Mal Aceh telah menerapkan sistem pelaporan sesuai dengan kedua standar yang dimaksud meskipun masih terdapat beberapa item yang tidak sesuai. Pada pelaporan keuangan menurut SAP, masih ditemukan ketidaksesuaian dalam penyajian informasi terkait pengadaan aset dan rincian penyusutannya. Adapun untuk laporan keuangan dengan PSAK 109, Baitul Mal Aceh sudah pernah menyajikannya dari tahun 2012-2017. Dari data yang tersedia, terdapat beberapa ketidaksesuaian penyajian laporan keuangan dengan PSAK 109. Dana amil dan dana non-halal tidak disajikan dalam laporan posisi keuangan serta tidak ada laporan perubahan aset kelolaan. Bahkan dalam dua tahun terakhir, tidak ada penyajian laporan keuangan ini dikarenakan keterbatasan sarana/perangkat pendukung dan sumber daya manusia yang tersedia.